The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.str.2016.03.025
|View full text |Cite|
|
Sign up to set email alerts
|

Structural Mechanism of Allosteric Activity Regulation in a Ribonucleotide Reductase with Double ATP Cones

Abstract: Ribonucleotide reductases (RNRs) reduce ribonucleotides to deoxyribonucleotides. Their overall activity is stimulated by ATP and downregulated by dATP via a genetically mobile ATP cone domain mediating the formation of oligomeric complexes with varying quaternary structures. The crystal structure and solution X-ray scattering data of a novel dATP-induced homotetramer of the Pseudomonas aeruginosa class I RNR reveal the structural bases for its unique properties, namely one ATP cone that binds two dATP molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 47 publications
(66 reference statements)
6
57
0
Order By: Relevance
“…Previous alignments of RRs have shown that loop 2 is wellconserved, consistent with its known role in allosteric regulation (16,19,(37)(38)(39). However, the current analysis revealed important differences among enzymes from different groups of eukaryotes.…”
Section: Phylogenetic Comparative Sequence Analysis Revealed Loop 2 Psupporting
confidence: 74%
“…Previous alignments of RRs have shown that loop 2 is wellconserved, consistent with its known role in allosteric regulation (16,19,(37)(38)(39). However, the current analysis revealed important differences among enzymes from different groups of eukaryotes.…”
Section: Phylogenetic Comparative Sequence Analysis Revealed Loop 2 Psupporting
confidence: 74%
“…An unexpected feature of the P. aeruginosa enzyme is the presence of 2 bound dATP molecules on one ATP cone and none on the other (6). Further heterogeneity in ATP/dATP coarse control was seen recently with the class Ib RNR from Bacillus subtilis (7).…”
mentioning
confidence: 87%
“…174,181 However, mounting evidence points to repeated gain and loss of the ATP cone throughout the evolutionary history of RNR, leading to the apparent variety of allosteric mechanisms observed today. A recent structure of the class I RNR from Pseudomonas aeruginosa in the presence of inhibiting dATP revealed an α 4 ring composed of two symmetry-related dimers 173 (Figure 17G). As in the α 6 ring seen in human RNR, this ring occludes access of the β subunit to the active site.…”
Section: Solution X-ray Scatteringmentioning
confidence: 99%
“…It is further thought that when regulation again became beneficial later in the enzyme’s history, a new ATP cone was incorporated rather than reversion of the original one to a functional state. 173 …”
Section: Solution X-ray Scatteringmentioning
confidence: 99%